2021
DOI: 10.1016/j.heliyon.2021.e08593
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influence of horticultural farming on selected water quality parameters in Maumau stream, a tributary of Nairobi River, Kenya

Abstract: This study aimed to determine the levels of contamination in Maumau stream as a result of horticultural activities in its vicinity. The stream was purposefully delineated into three blocks including upstream, midstream and downstream, where water samples were collected and analyzed for physicochemical attributes. Standard analytical procedures for water analysis were followed in laboratory analysis and the collected data was analyzed using Genstat software. Analyzed parameters include total dissolved solids (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This research highlights the complex interplay of pollution sources affecting water quality in the Nairobi River, including both urban and agricultural contributions. Wilson et al (2021) documented the impact of various sources of pollution on the Nairobi River. The study identified an area where wastewater from car wash operations joined the downstream, contributing to an increasing trend in water pollution along the stream course (Wilson, Michieka, & Mwendwa, 2021).…”
Section: State Of the Water Quality Of The Nairobi Rivermentioning
confidence: 99%
See 2 more Smart Citations
“…This research highlights the complex interplay of pollution sources affecting water quality in the Nairobi River, including both urban and agricultural contributions. Wilson et al (2021) documented the impact of various sources of pollution on the Nairobi River. The study identified an area where wastewater from car wash operations joined the downstream, contributing to an increasing trend in water pollution along the stream course (Wilson, Michieka, & Mwendwa, 2021).…”
Section: State Of the Water Quality Of The Nairobi Rivermentioning
confidence: 99%
“…Wilson et al (2021) documented the impact of various sources of pollution on the Nairobi River. The study identified an area where wastewater from car wash operations joined the downstream, contributing to an increasing trend in water pollution along the stream course (Wilson, Michieka, & Mwendwa, 2021). The increasing turbidity downstream was indicative of rising concentrations of metallic elements, anions, and alluviation due to siltation from cultivated land.…”
Section: State Of the Water Quality Of The Nairobi Rivermentioning
confidence: 99%
See 1 more Smart Citation